A Data‐Mining‐Assisted Design of Structural Colors on Diamond Metasurfaces. Issue 3 (2nd March 2022) - Jing, Jixiang; Yiu, Yau Chuen; Chen, Cong; Lei, Dangyuan; Shao, Lei; Wang, Qi; Li, Kwai Hei; Wong, Ngai; Chu, Zhiqin
Abstract : Structural Colors on Diamond Metasurfaces In article number 2100292, Ngai Wong, Zhiqin Chu, and co‐workers propose and demonstrate the concept of a low‐loss and high‐saturation color pixel design based on diamond metasurfaces. Moreover, a tensor completion‐based algorithm is introduced for the first time to assist the design of vivid colors, highly shortening the required runtime of simulation by 4 orders of magnitude.